Fall in circulating mononuclear cell mitochondrial DNA content in human sepsis - Pyle, Angela; Burn, David J.; Gordon, Charlotte; Swan, Catherine; Chinnery, Patrick F.; Baudouin, Simon V. (Intensive care medicine, 2010)
Purpose Loss of mitochondrial DNA (mtDNA) has been described in whole blood samples from a small number of patients with sepsis, but the underlying mechanism and clinical implications of this observation are not clear. We have investigated the cellular basis of the mtDNA depletion in sepsis, and determined clinical correlates with mtDNA depletion. Methods Whole blood samples were obtained from 147 consecutive patients with severe sepsis admitted to a General Critical Care Unit in a University Hospital and 83 healthy controls. In a separate study of 13 patients with severe sepsis, blood was obtained for immediate cell sorting by flow cytometry. MtDNA content was determined in whole blood DNA by PCR methods, and subsequently in the 13 samples where white cell subtypes were separated. Results The mtDNA content of peripheral blood in human subjects was lower in patients with sepsis than controls ( P < 0.0001). By studying leukocyte subsets in a subgroup of 13 patients, we showed that this was largely due to an increase in the proportion of circulating neutrophils, which contained ~3-fold less mtDNA than mononuclear leukocytes. However, isolated monocytes ( P = 0.041) and lymphocytes ( P = 0.021) from septic patients showed clear evidence of mtDNA depletion, which correlated with the APACHE II score ( P = 0.015). Conclusions In severe sepsis much of the apparent whole blood mtDNA depletion is due to a change in the differential leukocyte count. However mtDNA depletion in mononuclear cells occurs in patients with sepsis and correlates with disease severity.